Evaluation of regional innovation capability: an empirical study on major metropolitan areas in Taiwan - Dai, Yuan-Fung; Chu, Pin-Yu; Lu, Shih-Tong; Chen, Wei Tong; Tien, Yu-Chuen (Technological and Economic Development of Economy, 2022)
Establishing an analytical structure to classify proper criteria and identify the relative importance among them in different cities or municipalities for selection and resource allocations of government-sponsored regional innovation is crucial. In this paper, we construct an index system through the subject views of experts to evaluate regional scientific and technological innovation capabilities and collect empirical data to compare the six special municipalities in Taiwan by employing a hybrid CFPR-VIKOR approach. The research results show that a structural evaluation system is a basis for regional innovation policy. The need for fundamental data and regional resources assessments is apparent, and the role of the central government needs to be adapted to rapid changes. Through the design and adjustment of the regulatory system, decision-makers can decide how to allocate resources and further contribute to the development of regional innovation. We demonstrate that our approach can be extended to the regional innovation policies in the public sector.First published online 10 June 2022